Optimalisasi Keamanan Siber dan AI dalam Akselerasi Transformasi Digital Sektor Industri Sumatera Selatan - Deris Stiawan; Ahmad Heryanto; Nurul Afifah; Adi Hermansyah; Dian Palupi Rini; Septiani Kusuma Ningrum; Dendi Renaldo Permana (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to strengthen the digital defense system of PT PLN Palembang through the integration of cybersecurity technology and artificial intelligence (AI). As a strategic state-owned enterprise, PT PLN faces the risk of cyberattacks targeting SCADA and ERP systems, which may disrupt national energy resilience. The implementation method of this community service activity was carried out systematically through stages of infrastructure auditing, socialization, intensive training, and direct technology implementation using a participatory-collaborative approach. The instrument utilized in this activity was the SCADA system, which was analyzed through real-time network traffic monitoring using machine learning and deep learning algorithms. The results of this community service activity indicate the successful implementation of a SCADA-based security system capable of providing early detection of zero-day threats, as well as enhancing the capacity of PT PLN’s IT personnel in independently managing network security. The impact of this activity is the establishment of a more resilient and secure digital transformation foundation for industries in South Sumatra, while simultaneously reducing dependence on conventional passive security systems.